Propuesta de un tratamiento pasivo de DAM en base a un prototipo de dren anóxico calizo en el Crucero Nro. 4 de la mina La Veinticuatro, cantón Portovelo. - Aguilar Valarezo., Nixon José (2022)
The generation of acid mine drainage (AMD) is one of the leading environmental problems generated by mining activity and requires adequate treatment. In the present research, the passive technique of anoxic limestone drainage was evaluated on an experimental scale as an alternative to modifying the pH, electrical conductivity, turbidity, and presence of Cu, Fe, and Pb of the AMD of the Nro.4 cruiser of the La Veinticuatro mine of the Portovelo canton. For the realization of the experiment, eight simple AMD samples obtained previously at the same time were collected. At the same point as the affluent, these samples were stored at room temperature in plastic containers of 8 liters; four (n = 4) were randomly assigned s random to the experimental group and the remaining four (n=4) to the control group. The construction of the experimental prototype had dimensions (56.25 cm long; 15 cm wide; 15 cm deep), where 3.60 kg of limestone rock (n = 4) was used, and a volume of AMD of 7.2 L was treated for each repetition for 24 hours. The experimental prototype modified the initial conditions of the AMD, varying the pH from acid (2.73) to neutral (7.00) after 96 hours, while at 24 hours, the electrical conductivity gradually decreased (from 2476 uS/cm to 2062.30 uS/cm). Finally, the prototype showed high percentages of removal of metals Cu (71%), Fe (76%), and Pb (60%), becoming a successful passive treatment that aims to offer a viable alternative to treat AMD. Keywords: underground mining, acid mine drainage, limestone anoxic drainage, passive treatment.